SCIENTIFIC-PRACTICAL APPROACH TO FORMING THE SPATIAL LAYOUT OF ENTERPRISES - Rahimberdievich, Ubraimov Shukhratjon (Journal of Economic and Economic Policy, 2025)
Objective: This study aims to develop a scientifically grounded methodology for assessing and managing the economic potential of manufacturing enterprises undergoing structural, technological, and institutional transformations. Method: The research employs the principal component method and correlation-regression analysis to identify key indicators reflecting the structural transformation process. Empirical data from multiple enterprises over five years were analyzed using SPStatistics to construct correlation matrices and reduce variables to the most informative set. Results: Factor analysis revealed that the receivables-to-payables ratio and capital autonomy exert the most significant influence on overall economic potential. These indicators enable enterprise managers to make data-driven decisions, enhance structural efficiency, and improve competitiveness. Novelty: The study introduces an adaptive and comprehensive approach that integrates modern quantitative techniques into a practical framework for evaluating and managing economic potential. This methodology facilitates simplification of complex economic assessments and supports strategic adaptation, including digital transformation, in a dynamic economic environment.